A Tribute to the Work of Patricia Williams - Franke, Katherine (Columbia Journal of Gender and Law, 2014)
The task of selecting an honoree is not an easy one—as we aim to take up a corpus of work that is at once deep enough and broad enough to sustain a full day of conversation. To be honest, most legal scholars tend to be more hedgehogs than foxes, burrowing down deep into an area of law over the course of a career rather than bringing their intellectual talents to bear on a range of social problems or diverse disciplinary locations. One person, without question, stands out as an exception to this tendency in the legal academy, and that is the incredible Patricia Williams.